Design of a compensation scheme for environmental services for the basin of the Melendez River in the municipality of Cali, Colombia - Salazar Mancipe, Ángela María (Revista Colombiana de Investigaciones Agroindustriales, 2015)
CSAH - compensation for environmental services was used as a tool to solve or mitigate changes in the flow rates of the Melendez river, caused by the deterioration of forest cover in the upper middle part of the basin. The aim of this study was to develop a formula to set the value to compensate the owners and holders, depending on the attributes and environmental characteristics of the premises. By applying a mathematical formula the value determined to compensate for environmental services per hectare from the estimate of a base price and according to the ideal conditions of the premises to ensure water regulation: a) presence of streams b) existence of a buffer zone, c) presence of water sources, d) soil conditions, e) production systems. The offset value per year is between a minimum of $367,748 and a maximum of $735,496 (2015 prices), equal to the cost of opportunity estimated based on the four main crops in the upper and middle basin. These results emphasize the feasibility of compensation for environmental services, an exercise that will ensure conservation of watersheds that supply water to the population downstream. Para citar este artículo Salazar, A. (2015). Diseño de un esquema de compensación por servicios ambientales para la cuenca del río Meléndez en el Municipio de Santiago de Cali, Colombia. Rev. Colomb. Investig. Agroindustriales, 2(1), 25-40. DOI: http://dx.doi.org/10.23850/24220582.167